Design and fabricate a flexible toilet hose with spool - Abdullah Munzir, Zul Safaruddin (2012)
This thesis explains the process of designing and fabricating of flexible toilet hose with spool. Firstly, the current toilet hoses are studied. The studies include the design, advantages, disadvantages, materials, and installation. Later, three concepts are suggested to be chosen and concept 3 is selected for further studies which involving three dimensional modelling using SolidWorks 2011 software. During the modelling process, the dimensioning of design product is decided. The fabrication method of flexible toilet hose with spool is later decided. The fabrication of this hose includes the process of shearing, cutting, roll bending, welding, drilling, grinding, filing, and finishing. The fabrication scale is 1:1 finely pilot design. The found out of problems also included. The problems covered from the start till project ends. Lastly, the conclusion of the project is documented and given some recommendation for further studies on the project.